Wolman's disease and cholesteryl ester storage disorder: the phenotypic spectrum of lysosomal acid lipase deficiency. (September 2017) - Pericleous, Marinos; Kelly, Claire; Wang, Tim; Livingstone, Callum; Ala, Aftab
Summary: Lysosomal acid lipase deficiency is a rare, autosomal recessive condition caused by mutations in the gene encoding lysosomal acid lipase ( LIPA ) that result in reduced or absent activity of this essential enzyme. The severity of the resulting disease depends on the nature of the underlying mutation and magnitude of its effect on enzymatic function. Wolman's disease is a severe disorder that presents during infancy, resulting in failure to thrive, hepatomegaly, and hepatic failure, and an average life expectancy of less than 4 months. Cholesteryl ester storage disorder arises later in life and is less severe, although the two diseases share many common features, including dyslipidaemia and transaminitis. The prevalence of these diseases has been estimated at one in 40 000 to 300 000, but many cases are undiagnosed and unreported, and awareness among clinicians is low. Lysosomal acid lipase deficiency—which can be diagnosed using dry blood spot testing—is often misdiagnosed as non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH), hereditary dyslipidaemia, or cryptogenic cirrhosis. There are no formal guidelines for treatment of these patients, and treatment options are limited. In this Review we appraise the existing literature on Wolman's disease and cholesteryl ester storage disease, and discuss available treatments, including enzyme replacement therapy, oral lipid-lowering therapy, stem-cell transplantation, and liver transplantation.